Facilitators and barriers faced by community organizations supporting older adults during the COVID-19 pandemic - Kristen R. Haase; Ailsa C. Sirois; Dmitri Detwyler; Bahareh Kardeh; Shelley Peacock; Theodore D. Cosco; Marjan Kamali; Megan E. O’Connell (BMC Geriatrics)
Abstract Background During the COVID-19 pandemic, olderadult-focused community organizations played an essential role in supporting the wellbeing of older adults. Supporting older adults during this time required extensive modifications to existing programming but their adaptations during the COVID-19 pandemic are not well documented. The purpose of this study was to understand how older adult-focused community organizations adopted virtual delivery formats during the COVID-19 pandemic and their perspectives of the barriers and facilitators for organizations and older adults. Methods To understand the changes that were made, we conducted a qualitative environmental scan of community-based services across British Columbia. Online searches were complemented by snowball sampling and key informant interviews. We identified 90 older adult-serving community organizations and interviewed 26. We used reflexive thematic analysis to understand the main strategies. Results These community organizations described barriers related to older adults’ wellbeing, information technology proficiency, and personal/organizational losses related to changes in program structure. Facilitators for virtual activities and events included inter- and intra-organizational collaboration, intrinsic qualities of program design, physical resources to supporting virtual programming, and availability of technological resources. Organizations described meeting the challenge by increasing the ‘depth’ and ‘breadth’ of their reach. Conclusion Older adult-focused community organizations recognized the critical role they played for older adults and adapted their resources to meet those needs. Informational technology was quickly and effectively leveraged to promote social interaction for older adults when physical distancing was required during the COVID-19 pandemic. Barriers related to cost, time, and ultimately older adults’ interest in a virtual delivery format were critical limitations. Graphical Abstract